Innovative Protein Ingredients for Feeding Gilthead Seabream (Sparus aurata) Broodstock - Lucia Aidos; Giorgio Mirra; Mirko Sergio; Margherita Pallaoro; Maria Chiara Di Meo; Chiara Cialini; Chiara Bazzocchi; Silvia Clotilde Bianca Modina; Lorenzo Proietti; Luciano Foglio; Francisco Javier Alarcón-López; Katia Parati; et al. (Aquaculture Nutrition, 2025)
A feeding trial with alternative protein sources was conducted in gilthead seabream (Sparus aurata, L.) broodstock fed a control diet and two diets with 5% or 10% inclusion levels of a blend of novel ingredients. The blend is composed of 40% insect (Hermetia illucens), 10% duckweed (Lemna minor), 45% Nannochloropsis gaditana, and 5% Alaria esculenta meal dry biomass. The animals were reared in a recirculating aquaculture system and administered the experimental diets 3 months before spawning and for a total of 7 months. Fertilized eggs were incubated until hatching and newly hatched larvae were monitored until the yolk sac absorption stage. High inclusion (HI; 10%) of novel ingredients to broodstock resulted in a significantly higher hatching rate, while both groups fed novel ingredients produced offspring with significantly higher survival until the end of the yolk sac stage compared to offspring from parents fed the control diet (p<0.05). The inclusion of the protein blend at any level did not produce differences in larval growth. Morphological and histometric analyses in larvae revealed hypertrophic growth during the yolk sac stage. The expression of genes involved in muscle development and growth indicated no differences in growth potential in larvae between groups. Overall, broodstock feeds for gilthead seabream can have an inclusion of novel ingredients without a negative impact on larval performance and growth. Further studies are needed to study the long-term effects of broodstock diet on offspring quality.